CTIM-10. A PHASE II STUDY OF RETIFANLIMAB (PD-1 INHIBITOR) IN COMBINATION WITH BEVACIZUMAB AND HYPOFRACTIONATED RADIOTHERAPY FOR RECURRENT GLIOBLASTOMA: NCT03532295. (14th November 2022) - Butt, Omar; Huang, Jiayi; Luo, Jingqin; Tao, Yu; Strowd, Roy; Hissim, Deanna; Kizilbash, Sani; Abraham, Christopher; Anstass, George; Johanns, Tanner; Kim, Albert; Ciorba, Matthew; et al.
Abstract: INTRODUCTION: Immunotherapies targeting PD-1 in recurrent glioblastoma (rGBM) have shown limited activity. We hypothesize combining therapies targeting immunosuppressive pathways with cytotoxic and antiangiogenic therapies will improve survival. This nonrandomized, noncomparative Phase II study examines safety and efficacy of an anti-PD-1 monoclonal antibody (retifanlimab), hypofractionated radiotherapy (HFRT), and bevacizumab, with or without an IDO1 inhibitor (epacadostat), in patients with rGBM. METHODS: This is an open-label Phase II study of two regimens. Regimen A examines retifanlimab (500mg IV Q4W) + bevacizumab (10mg/kg IV Q2W) + HFRT (3.5Gy/day x 10) in patients with IDH1/2-WT rGBM. Regimen B adds epacadostat. Key inclusions include dexamethasone ≤ 4 mg/day and reirradiation candidacy. The primary endpoint is overall survival (OS) probability at 9 months (OS-9). An increase of OS-9 from 38% (bevacizumab alone) to 60% was considered clinically relevant and required 24 efficacy evaluable patients. RESULTS: Regimen A accrual is complete; interim results are as follows: 26 rGBM enrolled, with 24 evaluable [median age 64.2 years (42.1-81.8); 29% female; 29% MGMT promotor methylated; 33.3% with multi-focal disease; median KPS 90 (70-100); median baseline dexamethasone 0 mg (0-4) and ALC 1, 000 cells/µl (300-3, 700)]. Patients received a median of 6 cycles as of May 2022 (2-24). Median follow-up is 16.0 months. Interim median PFS is 7.0 months (95%CI: 4.5~11.1) and median OS is 12.2 months (95%CI 7.1~18.0). Regimen A met primary endpoint with OS-9 of 67% (95%CI: 44~82%). Overall response rate is currently 58% (95%CI: 36.94~77.2%). There were five possible immune-related grade 3+ toxicities to date (n = 1 each colitis, vomiting, and seizure; n = 2 diarrhea). Regimen B is enrolling. CONCLUSIONS: Interim analysis suggests combination retifanlimab, HFRT, and bevacizumab in rGBM is generally well-tolerated, with encouraging OS and PFS at the time of submission. Correlative analysis is ongoing and will be presented at the meeting.